Globalisasi Dan Lingkungan Ekonomi Di Indonesia: Sebuah Analisis Tentang Dampak Dan Tren - Feronica Simanjorang; Achmad Fattahillah; Dolok Saribu Irfan; Gantari Firjatullah; Ida Maria Pangaribuan; Mustafa Baga (JURNAL RISET MANAJEMEN (JURMA), 2023)
Globalization is the result of technological progress and innovation. Advances in technology have opened the door for increasing the volume of international trade through globalization. With such developing technology, it has made international transactions an easier and faster process for all countries to use. This is unavoidable because countries often have their own environment, so that globalization in this case has implications for expansion beyond national borders. The method of writing literature review articles is the library research method which originates from online media such as Google Scholar, Mendeley and other academic online media. Through this article, the author will reveal the influence of globalization on the Indonesian economic sector. The results confirm that an unbalanced reliance on careless international transactions can threaten local businesses, but also support Indonesian products that are known in other countries. This study shows that globalization in general has a very large positive impact on Indonesia, but the government as a whole must be aware of the negative impacts that can cause losses to local businesses due to globalization.